Dual T-type and L-type calcium channel blocker exerts beneficial effects in attenuating cardiovascular dysfunction in iron-overloaded thalassaemic mice - Kumfu S. (2017)
© 2016 The Physiological Society. New Findings: What is the central question of this study? Head-to-head comparison of the therapeutic efficacy among commercial iron chelators and a dual T- (TTCC) and L-type calcium channel (LTCC) blocker on cardiac function, mitochondrial function and the protein expression of cardiac iron transporters in thalassaemic mice in iron-overloaded conditions has not been assessed. What is the main finding and its importance? The dual TTCC and LTCC blocker efonidipine could provide broad beneficial effects in the heart, liver, plasma and mitochondria in both wild-type and thalassaemic mice in iron-overloaded conditions. Its beneficial effects are of the same degree as the three commercial iron chelators currently used clinically. It is possible that efonidipine could be an alternative choice in patients unable to take iron chelators for the treatment of iron-overload conditions. Iron chelation therapy is a standard treatment in thalassaemia patients; however, its poor cardioprotective efficacy and serious side-effects are a cause for concern. Previous studies have shown that treatment with L-type calcium channel (LTCC) blockers or dual T-type calcium channel (TTCC) and LTCC blockers decreases cardiac iron and improves cardiac dysfunction in an iron-overloaded rodent model. Currently, the head-to-head comparison of therapeutic efficacy among commercial iron chelators, a dual TTCC and LTCC blocker and an LTCC blocker on cardiac function, mitochondrial function and the protein expression of cardiac iron transporters in thalassaemic mice in an iron-overloaded state has never been investigated. An iron-overloaded state was induced in β-thalassaemic and wild-type mice. Cardiac iron overload was induced to a greater extent than in a previous study by feeding the mice with an iron-enriched diet for 4 months. Then, an LTCC blocker (amlodipine) or a dual TTCC and LTCC blocker (efonidipine) or one of the commercial iron chelators (deferoxamine, deferasirox or deferiprone) was administered for 1 month with continuous iron feeding. All treatments reduced cardiac iron deposition and improved mitochondrial and cardiac dysfunction in both types of mice. Only efonidipine and the iron chelators reduced liver iron accumulation, liver malondialdehyde and plasma malondialdehyde in these mice. Although all pharmacological interventions reduced cardiac iron deposition, they did not alter the protein expression levels of cardiac iron transporter. These findings indicated that efonidipine provided all benefits to the same degree as the three commercial iron chelators. These findings indicate that a dual TTCC and LTCC blocker could be beneficial for treatment of an iron-overloaded state.